2008
DOI: 10.1007/s10815-008-9246-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 and CYP1B1 genetic polymorphisms and uterine leiomyoma risk in Chinese women

Abstract: Purpose The aim of the study was to evaluate the association of CYP1A1 and CYP1B1 polymorphisms with uterine leiomyoma in Chinese women. Methods We investigated 100 women with clinically diagnosed uterine leiomyoma and 110 healthy normal subjects from Chinese women. The genetic distribution of two CYP1A1 polymorphisms at MspI, Ile462Val and four CYP1B1 polymorphisms at Arg48Gly, Ala119Ser, Leu432Val, Asp449Asp were analyzed by polymerase chain reactionrestriction fragment length polymorphism and DNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
2
20
4
Order By: Relevance
“…However, similar to the findings of the present study, there was no association between polymorphisms of the CYP1B1 gene and UL susceptibility in China. Despite the results of Ye et al (17) in Chinese females, El-Shennawy et al (14) observed an elevated risk of UL in females with the CC genotype of the CYP1B1 Leu432Val (C/G) polymorphism and according to their results this genotype can predict the susceptibility to UL in Egyptian females. Shen et al (27,28) studied the association between the Ala119Ser, Leu432Val and Asp449Asp polymorphisms of the CYP1B1 gene and UL in Han Chinese females.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, similar to the findings of the present study, there was no association between polymorphisms of the CYP1B1 gene and UL susceptibility in China. Despite the results of Ye et al (17) in Chinese females, El-Shennawy et al (14) observed an elevated risk of UL in females with the CC genotype of the CYP1B1 Leu432Val (C/G) polymorphism and according to their results this genotype can predict the susceptibility to UL in Egyptian females. Shen et al (27,28) studied the association between the Ala119Ser, Leu432Val and Asp449Asp polymorphisms of the CYP1B1 gene and UL in Han Chinese females.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have addressed the association between the genetic polymorphisms of enzymes involved in the estrogen metabolism and the occurrence of UL (14,17,26,27). In 2006, Herr et al (26) reported a significant correlation between CYP2A13 and CYP1A1 SNPs and UL in a Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most well-studied SNP locus on CYP1A1 is rs1048943, which involves a G→A transversion, leading to the substitution of 462Ile with Val [20]. This transversion is reported to increase the risk of UL development in a Chinese population [21]. In the present study, the frequencies of the mutant genotype G/A+G/C mutation on the rs1048943 locus (34.9%, 19.5%) and G/A+A/A mutation on the rs4646422 locus (34.2%, 15.9%) were higher in UL tissues than that in the control tissues (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%